Left upper lobe atelectasis due to plastic bronchitis - Tuğba Şişmanlar; Ayşe Tana Aslan; Çiğdem Öztunalı; Öznur Boyunağa (The Turkish Journal of Pediatrics)
Plastic bronchitis is a rare condition in children, characterized by expectoration of branching bronchial casts. It can cause atelectasis in the lung. Herein we reported a 4.5-year-old boy with left upper lobe atelectasis due to plastic bronchitis. Although his chest X-ray is specific for left upper left atelectasis, thoracic computerized tomography had been performed and was compatible with obliterated left upper lobe bronchus. Typical radiological appearance of the left upper lobe atelectasis is not well known by clinicians which results unnecessary further examinations such as computerized tomography which exposes high dose radiation. We want to emphasize the long-term side effects of radiation and avoid unnecessary examinations in children.